Comparative study of the Mexico debt crisis and the Asian currency crisis : lessons for LDCs. - Woon, Tai Keat. (2008)
This paper comparatively studies the Mexican currency crisis of 1994-1995 and the Asian crisis which began in July 1997. Specifically, the Asean three countries consisting of Thailand, Indonesia and Malaysia will be examined more closely in the Asian case. I examine whether the usual factors cited as causes of the two crises are indeed relevant for the two economic entities.